Study the Effect of Sources of Manufacturing Companies on the Achievement of the Objectives of the Trade Exhibition: Case Study at the International Exhibition of Bushehr City - Majid Esmaeilpour; Manijeh Bahrainizadeh (تحقیقات بازار یابی نوین, 2016)
Background: With increasing competition and reducing the possibility of exposure to commodities, the possibility of participating in trade exhibition is important hundredfold. Exhibiting a great opportunity for companies provide the goods. The exhibition will present a pre-determined targets and long-term planning to achieve these goals, the recognition of its resources in setting goals as a fundamental principle of the company, is participating in the exhibition. Objectives: The purpose of this study was to assess the importance sources of participating in trade exhibition and the impact that it will have sources of to achieve the objectives of the exhibition. Methodology: The study in term of purpose is applied and in term of data collection is descriptive - and the correlation. The research includes companies participating in international exhibition Bushehr over 180 companies. This study used a sample of 120 companies was Morgan. Data derived from the survey questionnaire. Validity through the content validity and reliability through Cronbach's alpha was approved. Data Analysis is a method of structural equation modeling. Results and findings: The results obtained suggest that the booth personnel sources of, sources of exhibition have a significant impact on sales targets and management capabilities. The booth personnel sources of and the ability to communicate with customers also have a significant impact on sales purposes. The findings of this study it can be concluded that except for the purposes of sale and non-sale capabilities partnership that does not, improvement of existing resources and capabilities of each model achieves sales targets and other participants will sell.